2003
DOI: 10.1210/jc.2002-021883
|View full text |Cite
|
Sign up to set email alerts
|

Hypoadiponectinemia Is Closely Linked to Endothelial Dysfunction in Man

Abstract: Vascular endothelial dysfunction has been demonstrated in overweight or obese patients, but the molecular basis for this link has not been clarified. We asked what the relationship was between adiponectin, an adipose-specific molecule, and endothelial function. Forearm blood flow (FBF) was measured during reactive hyperemia by using strain-gauge plethysmography in 76 Japanese subjects without a history of cardiovascular or cerebrovascular disease, diabetes mellitus, hepatic, or renal disease. The peak FBF and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
223
4
9

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(244 citation statements)
references
References 23 publications
8
223
4
9
Order By: Relevance
“…Studies of the association between adiponectin levels and vascular reactivity have been inconclusive in both normal and hyperglycaemic populations. A positive relationship between adiponectin and peak forearm blood flow was found in both healthy [25] and hypertensive Japanese subjects [26]. Tan et al described a positive relationship between adiponectin and EDV both in healthy and in type 2 diabetic persons [27].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Studies of the association between adiponectin levels and vascular reactivity have been inconclusive in both normal and hyperglycaemic populations. A positive relationship between adiponectin and peak forearm blood flow was found in both healthy [25] and hypertensive Japanese subjects [26]. Tan et al described a positive relationship between adiponectin and EDV both in healthy and in type 2 diabetic persons [27].…”
Section: Discussionmentioning
confidence: 97%
“…In brief, after an overnight fast and the collection of baseline samples, Dextrose 0.3 g/kg was administered intravenously, followed 20 min later by the intravenous infusion of insulin 0.03 U/kg (Humulin R; Eli Lilly, Indianapolis, IN, USA). Samples were collected for insulin and glucose at 2, 3, 4, 5,6,8,10,12,14,19,22,23,24,25,27,30,40,50,60,70,80, 90, 100, 120, 140, 160 and 180 min following the dextrose and analysed using the Bergman's Minimal Model, a computer-based method to assess plasma insulin and glucose dynamics during an IVGTT. The minimum model for glucose disposal and insulin dynamics yields assessments of insulin secretion and sensitivity, including the insulin sensitivity index (S I ) and the glucose effectiveness index (S G ) also known as insulin-independent glucose clearance.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, adiponectin, an adipose tissue-derived peptide, plays an important role in glucose and lipid metabolism (Karbowska and Kochan 2006), and its secretion is markedly downregulated in obesity-related conditions, such as insulin resistance and diabetes (Kern et al 2003). Furthermore, clinical observations have demonstrated that hypoadiponectinemia has a close relationship with endothelial dysfunction of peripheral arteries (Shimabukuro et al 2003) and that plasma total adiponectin levels are inversely related to the risk of cardiovascular events (Kumada et al 2003). Despite the wealth of knowledge on adiponectin in established obesity and CVD, long-term studies on the effect of diet are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…[97][98][99] There is evidence that all of these obesity-related peptides alter vascular tone or function. [100][101][102][103] Additionally, resistin, adiponectin and ghrelin all influence the expression of CAMs on vascular endothelial cells. [104][105][106] Childhood obesity and atherosclerosis MR Skilton and DS Celermajer Finally, the physical stresses that accompany increases in body mass may contribute to cardiovascular disease.…”
Section: Mechanisms Linking Obesity and Atherosclerosismentioning
confidence: 99%